Technology foresight in Modular Construction Shipbuilding Industries: The Case of Malaysia’s Shipyard - Mokhtar, Ahmad Alliff Anuar; Amir, Mohamad Abu Ubaidah; Hafizah, Ainnur; Halim, Abdul (International Journal of Engineering and Technology, 2018)
The shipbuilding and ship repair industry in Malaysia involves designing, building and constructing, repairing and maintaining, converting and upgrading of vessels as well as marine equipment. It is getting larger and always evolve in line with the development of technology such as with the latest technology which is embedded in modular construction. Nowadays, the modular construction approach in shipbuilding is already known worldwide. However, adoption of this method in Malaysia is still minimal in term of scale and it is not comprehensive. The latest, Boustead Naval Shipyard (BNS) was entrusted to build 6 Littoral Combat Ship (LCS) for Royal Malaysian Navy (RMN) in BNS in Lumut, Malaysia. One of the advantages for this contract is the technology transfer which also includes the modular construction. The study is conducted using the qualitative and quantitative method. Qualitative data collection method that used in this study includes individual interviews, and observations to examine the perspective from the higher management level on how to assess modular construction shipbuilding and hence to examine the factors through implementation and the effectiveness towards Malaysia’s shipyard of modular construction shipbuilding. For quantitative data collection method include various forms of surveys – online and form survey. Respondents are only from the higher management level. This data will be transformed into usable statistics using statistical software, Statistical Package for the Social Sciences (SPSS). Thus, this study is to analyse the technology and the viability in which to investigate of the existing business sustainability construction shipbuilding in Malaysia’s Shipyard. The result can be used for the better understanding the modular construction and its impact on the production process in Malaysia, and also improve the technology and method of modular construction shipbuilding in Malaysian shipyard.